Design and pharmacological characterization of VUF14480, a covalent partial agonist that interacts with cysteine 983.36 of the human histamine H4 receptor. (15th August 2013) - Nijmeijer, S; Engelhardt, H; Schultes, S; van de, A C; Lusink, V; de, C; Wijtmans, M; Haaksma, E E J; de, I J P; Stachurski, K; Vischer, H F; Leurs, R
<x xml:space="preserve">Abstract</x> Background and Purpose The recently proposed binding mode of 2‐aminopyrimidines to the human (h) histamine H4 receptor suggests that the 2‐amino group of these ligands interacts with glutamic acid residue E1825.46 in the transmembrane (TM) helix 5 of this receptor. Interestingly, substituents at the 2‐position of this pyrimidine are also in close proximity to the cysteine residue C983.36 in TM3. We hypothesized that an ethenyl group at this position will form a covalent bond with C983.36 by functioning as a Michael acceptor. A covalent pyrimidine analogue will not only prove this proposed binding mode, but will also provide a valuable tool for H4 receptor research. Experimental Approach We designed and synthesized VUF14480, and pharmacologically characterized this compound in hH4 receptor radioligand binding, G protein activation and β‐arrestin2 recruitment experiments. The ability of VUF14480 to act as a covalent binder was assessed both chemically and pharmacologically. Key Results VUF14480 was shown to be a partial agonist of hH4 receptor‐mediated G protein signalling and β‐arrestin2 recruitment. VUF14480 bound covalently to the hH4 receptor with submicromolar affinity. Serine substitution of C983.36 prevented this covalent interaction. Conclusion and Implications VUF14480 is thought to bind covalently to the hH4 receptor‐C983.36 residue and partially induce hH4 receptor‐mediated G protein activation and β‐arrestin2 recruitment. Moreover, these observations confirm our previously proposed binding mode of 2‐aminopyrimidines. VUF14480 will be a useful tool to stabilize the receptor into an active confirmation and further investigate the structure of the active hH4 receptor. Linked Articles This article is part of a themed issue on Histamine Pharmacology Update. To view the other articles in this issue visit http://dx.doi.org/10.1111/bph.2013.170.issue‐1